Bisnicalaterines B and C, atropisomeric bisindole alkaloids from hunteria zeylanica, showing vasorelaxant activity - Hirasawa, Y.; Hara, M.; Nugroho, A.E.; Sugai, M.; Zaima, K.; Kawahara, N.; Goda, Y.; Awang, K.; Hadi, A.H.A.; Litaudon, M.; Morita, H. (American Chemical Society, 2010)
Two new bisindole alkaloids, bisnicalaterines B and C (1 and 2) consisting of an eburnane and a corynanthe type of skeletons, were isolated from the bark of Hunteria zeylanica. Their absolute structures were determined by combination of NMR, CD, and computational methods, and each of them was shown to be in an atropisomeric relationship. Bisnicalaterines B and C (1 and 2) showed potent vasorelaxant activity on isolated rat aorta.